Mathematical Modeling in Systems Biology (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint presents a collection of systems biology-related topics and new studies that utilize computational, mathematical, and systems-oriented approaches to reveal important aspects of various biological problems.